Sialylation of CD55 by ST3GAL1 Facilitates Immune Evasion in Cancer - Wender Lin; Tan‐Chi Fan; Jung‐Tung Hung; Hui-Ling Yeo; Sheng‐Hung Wang; Chu‐Wei Kuo; Kay‐Hooi Khoo; Li‐Mei Pai; John Yu; Alice L. Yu (2020)
Abstract Altered glycosylations, which are associated with expression and activities of glycosyltransferases, can dramatically affect the function of glycoproteins and modify the behavior of tumor cells. ST3GAL1 is a sialyltransferase that adds sialic acid to core 1 glycans, thereby terminating glycan chain extension. In breast carcinomas, overexpression of ST3GAL1 promotes tumorigenesis and correlates with increased tumor grade. In pursuing the role of ST3GAL1 in breast cancer using ST3GAL1-siRNA to knockdown ST3GAL1, we identified CD55 to be one of the potential target proteins of ST3GAL1. CD55 is an important complement regulatory protein, preventing cells from complement-mediated cytotoxicity. CD55 had one N-linked glycosylation site in addition to a Ser/Thr-rich domain, which was expected to be heavily O-glycosylated. Detailed analyses of N- and O-linked oligosaccharides of CD55 released from scramble or ST3GAL1 siRNA–treated breast cancer cells by tandem mass spectrometry revealed that the N-glycan profile was not affected by ST3GAL1 silencing. The O-glycan profile of CD55 demonstrated a shift in abundance to nonsialylated core 1 and monosialylated core 2 at the expense of the disialylated core 2 structure after ST3GAL1 silencing. We also demonstrated that O-linked desialylation of CD55 by ST3GAL1 silencing resulted in increased C3 deposition and complement-mediated lysis of breast cancer cells and enhanced sensitivity to antibody-dependent cell-mediated cytotoxicity. These data demonstrated that ST3GAL1-mediated O-linked sialylation of CD55 acts like an immune checkpoint molecule for cancer cells to evade immune attack and that inhibition of ST3GAL1 is a potential strategy to block CD55-mediated immune evasion.